Assessment of Information Technologies for Teaching and Learning at Rivers State University, Nkpolu-Oroworukwo, Port Harcourt - Jamaica, Nengi Jessy; Sam-Kalagbor, Victoria Osaruchi (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
It is essential for lecturers and students to maintain above-average proficiency in information technology to ensure competence and effectiveness in teaching and learning, particularly in Rivers State University, Port Harcourt. This study aimed to assess students' use of information technology in the university. It was guided by three objectives, three research questions, and three hypotheses, employing a descriptive survey research design. The study's population comprised 31,048 individuals, including 1,109 academic staff and 29,939 students. A sample size of 689 participants, 294 students and 395 lecturers was determined using the Taro Yamane formula. The stratified random sampling technique was adopted for participant selection. Data were collected using the Assessment of Information Technologies for Teaching and Learning in Rivers State University, Port Harcourt Questionnaire, rated on a four-point scale and validated by experts. The instrument's reliability was established using Cronbach's Alpha, yielding coefficients of 0.75, 0.79, and 0.81 for its three clusters. Researchers, with the assistance of research aides, distributed 689 copies of the questionnaire. Data analysis was conducted using mean and standard deviation to address research questions, while hypotheses were tested using a z-test at a 0.05 significance level, with a critical value of ±1.96. Findings indicated that computers, application software, and the internet are integral to teaching and learning at Rivers State University. Furthermore, no significant difference was found between lecturers and students regarding their use of these technologies. Based on these findings, it was recommended that the university management implement regular training and workshops to enhance students’ and faculty members' proficiency in using computers, application software, and internet resources for academic purposes. The university should allocate resources to procure and maintain advanced application software tailored to various disciplines, ensuring students and lecturers have access to cutting-edge tools that support learning and research.